UPAYA PENINGKATAN PERUSAHAAN DALAM PELAKSANAAN REVEGETASI PASCATAMBANG DI PT. BINUANG MITRA BERSAMA - Ahdyannor, Muhammad Isra; Kissinger, Kissinger; Priatmadi, Bambang Joko; Badaruddin, Badaruddin (EnviroScienteae, 2021)
Indonesia Is a country that has a wealth of natural resources, the Coal Mining Commodity is one of the natural resources exploited in Indonesia. The exploitation of coal cannot be separated from environmental impacts. The environmental impacts of open-pit mining activities include: decreased soil productivity, soil compaction, erosion and sedimentation, soil movement, disruption of flora and fauna, disruption of security and health of the population, and changes in micro-climate. Reclamation is an activity carried out during the stages of a mining business to organize, restore and improve the quality of the environment and ecosystem so that it can function again. The research method in this research is to assess the success of the implementation of reclamation in accordance with the Permenhut Nomor P.60 Menhut-II/ 2009. In assessing the success of reclamation implementation, the stages of activities carried out are surveys, reference studies, sampling, scoring and weighting, and analysis. The implementation of reclamation at PT Binuang Mitra Bersama can be concluded that it is known that the Achievement of Land Arrangement based on the weight value obtained a figure of 28.5 from a maximum weight value of 30, Achievement of Erosion and Sedimentation Control based on the weight value obtained a number of 10 from a maximum weight value of 20, Planting achievement based on the weight value obtained a number of 26 from the maximum weight value of 50. The total value calculation is obtained by a value of 63.5 which indicates that the results of the reclamation implementation are included in the Medium criteria or the results of the reclamation implementation are accepted, provided that improvements are needed to reach a value of> 80.